Axisymmetric model for Taylor impact test and estimation of metal plasticity using nonlinear deformation profile - Narayan; Khan D.; Chakraborty S. (My University, 2025)
In this research article, an existing axisymmetric model for the Taylor impact test has been refined by deriving new governing equations, reducing approximations, relaxing assumptions and preserving the veritableness of the phenomenon to a better extent. It has been shown in most of the experimental results that the deformation profile of the Taylor impact specimen is nonlinear but to derive governing equations, researchers conventionally use linear profile. Main reforms include relaxing the conventional assumptions by considering the deformation profile as smooth/nonlinear (differentiable and continuous both) for connecting the deformed and the undeformed parts because in reality they are invisibly coherent. Unlike the previous axisymmetric model where the slope of the mushrooming zone is approximated with a constant, in the present model it has been taken as a function of varying longitudinal distance. The governing equations in the present axisymmetric model have been solved using MATLAB software. In comparison to the deformation measurements and time history results based on finite element commercial code LS-DYNA, modified smooth particle hydrodynamics (MSPH) and previous axisymmetric model, the current simulated results have been found to be improved and matching more closely with the experimental data. © 2023, The Author(s), under exclusive licence to The Brazilian Society of Mechanical Sciences and Engineering.